Pola Permintaan Daging Tingkat Rumah Tangga di Indonesia: Analisa Data Mikro 2013 - Nugroho, Sigit; Suparyono, Sita Wardhani (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
The objective of this study is to understand the meat demand pattern of household in Indonesia. This study used the 2013 National Socio-Economic Survey (SUSENAS) and Agricultural Census (SP). The method used to understand the meat demand pattern is Quadratic Almost Ideal Demand System (QUAIDS) approach with Iterated Linear Least Square (ILLS) estimator. The result shows that urban, education, household size, and domestic meat supply have an influence on meat demand pattern and its elasticity.